Critique of Stable Gender Roles in Markus Zussak’s The Book Thief - Gurung, Golman (Journal of Development Review, 2021)
The major characters in the novel The Book Thief perform their gender roles in a way that defies the notion of gender roles as a fixed category and it goes against the conventional idea of what weunderstand by gender. Traditional gender roles see males as masters and decision makers and women as caregiver who confines themselves within the four walls of the house. The present novel critiques and challenges those ideas through the actions and behavior of the main characters. It becomes clear from the observation that the male and female characters in the novel deviate from the roles that are assigned to them conventionally. Because of the impact of war males perform feminine roles and females act as masculine characters. For this kind of analysis of the novel, the present paper borrows ideas from Judith Butler, Judith Halbestam and other critics whose theoretical concepts have to do with the porosity of gender roles. It is an indication that gender roles are not stable and can undergo change as per the change in time and the change in the behavior and activities of the characters.